A Visualization Framework for Synthesizing Spatial Impacts from Multiple Site Factors. Issue 2 (1st May 2017) - Dai, Linlin; Wan, Li; Gai, Shijie
Abstract : This paper presents the development of a modelling framework for synthesizing and visualizing the spatial impacts of multiple factors with respect to the project site in architectural and urban design. In design practice, collecting and processing the information about the project site is critical to the final outcome of the design proposal. Given the complexity observed in our built-up environment, the information that architects need to process and respond to is enormous in terms of magnitude and variety. The proposed modelling framework aims to quantify the spatial impacts of various site factors on a consistent basis. The significance of this research lies in synthesizing the impacts from multiple factors through a digital interface. The three-dimensional form of data representation within the digital context may inspire schematic thoughts of architects. By adjusting the parameterization of each factor, architects can prioritize the design issues and explore a wide spectrum of design schemes.